Short-Term Outcomes of Transabdominal Preperitoneal Ventral Hernia Repair With Rectus Aponeuroplasty (TAPPRA) for the Management of Incisional Hernias - Maggie E. Bosley; Zev Felix; Gustavo Salgado-Garza; Shan Lansing; Vahagn C. Nikolian (Journal of Abdominal Wall Surgery)
IntroductionOptions for minimally invasive ventral hernia repair continue to evolve as a function of our understanding of the abdominal wall and the development of new techniques. We describe a robotic transabdominal pre-peritoneal repair with concurrent rectus aponeuroplasty (TAPPRA) for incisional and recurrent ventral hernias.MethodsAll patients in this retrospective cohort study underwent TAPPRA repair between October 2023 and March 2024. This study aimed to determine intraoperative feasibility of the technique and to assess immediate postoperative outcomes.ResultsTwelve patients underwent TAPPRA repair for incisional and/or recurrent ventral hernias at an academic hernia center. The median case duration was 135 min with no significant intraoperative complications noted. Average defect size for the hernias measures 6.5 × 8.5 cm. Polypropylene mesh was used to reinforce all defects, with the average dimensions being 19.7 × 21.5 cm. 83% of patients were discharged within 24 h of their procedure. No significant postoperative complications were noted.ConclusionWe describe the first use of a novel ventral hernia repair technique, TAPPRA, and demonstrate that it is safe, feasible, and associated with appropriate short-term outcomes for repair of moderate sized incisional hernias.